Pharmacotherapy of Lung Transplantation: An Overview. (February 2013) - Thompson, Melissa L.; Flynn, Jeremy D.; Clifford, Timothy M.
Lung transplantation has become a viable treatment therapy for end-stage lung disease patients. The most common etiologies of end-stage lung disease, which can require a transplant are chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis (IPF), pulmonary arterial hypertension (PAH), and pulmonary fibrosis (PF). Listing criteria are institution and program specific. Approximately 1500 lung transplants were performed in 2008; and at 5 years post transplant, one-half are expected to survive. The surgery itself is associated with various complications, including surgical, infectious, and mechanical. Immunosuppression is paramount to the management of these patients, the goal being prevention of T cell activation to prevent rejection of the new organ. The patients commonly receive an induction agent with a T cell depleting antibody and high-dose corticosteroids. Maintenance immunosuppression begins immediately after the surgery, consisting of a combination of a calcineurin inhibitor, antimetabolite, and corticosteroids. Side effect profiles from the various agents will determine the choice of agents, and patients may have modifications throughout the therapy. The role of the pharmacist spans the inpatient management of acute complications to medication selection, management of maintenance immunosuppression, as well as monitoring for adverse drug reactions and drug–drug interactions. A multidisciplinary collaborative approach must be taken to ensure the best outcomes for this patient population.